Apatite Geochemical Perspectives on the Maturation of Continental Arc Crust via Mush‐Facilitated Processes During Magmatic Flare‐Up - Long Chen; Peng Gao; Ian Somerville; San‐Zhong Li; Jiang‐Hong Deng; Dong‐Yong Li; Sheng‐Yao Yu; Xiao‐Hui Li; Hua‐Hua Cao; Zi‐Fu Zhao; Zhi‐Feng Yin (Geochemistry, Geophysics, Geosystems)
Abstract In volcanic arcs, magma evolves from basaltic to intermediate and felsic composition, resulting in arc crust maturation. It remains unclear whether processes involving mush during magmatic flare‐ups would enhance this evolution. This study revealed a temporal‐compositional evolution of plutonic rocks from mafic (∼94 Ma) to intermediate (∼92–88 Ma) to felsic (∼88 Ma) during a magmatic flare‐up event in the Gangdese arc, Tibet, with increasing radiogenic Sr–Nd isotope enrichment. Apatites in mafic and felsic rocks have εNd(t) values similar to their hosts, while intermediate rocks show higher values. The elemental composition of apatites in mafic and intermediate rocks is similar but differs from those in felsic rocks. Textural and compositional features indicate varying degrees of influence of mafic rock compositions by accumulation. Triangular and linear covariation relationships between apatite‐compatible (e.g., La) and ‐incompatible (e.g., Rb) elements with SiO2, respectively, for all plutonic rocks as a whole, confirm the incorporation of apatite‐rich mushes into the mixing process. These findings suggest that mafic magma crystallized into apatite‐rich mush, which was later remobilized and mixed with felsic magma to form intermediate magma. Felsic rocks represent end‐member magmas resulting from crustal anatexis and/or mafic magma differentiation. Thus, the Gangdese arc's maturation during the magmatic flare‐up progressed sequentially through mafic magma crystallization and mush formation, mush remobilization and mixing with felsic magma, and the eventual accumulation and segregation of felsic magma. This sequence of events during flare‐ups illustrates a common crustal maturation process in volcanic arcs, as also seen in the Andean Cordillera.